2022
DOI: 10.1007/s40120-022-00408-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Symptom Burden and Impact of Myasthenia Gravis from the Patient’s Perspective: A Qualitative Study

Abstract: Introduction: Patients with generalized myasthenia gravis (gMG) experience functional impairment due to MG symptoms. This study aimed to assess, from the patient perspective, the symptoms, impacts, and treatment goals of individuals diagnosed with gMG. Methods: Semi-structured, in-depth conceptelicitation interviews were conducted with 28 individuals diagnosed with gMG in the United States.Results: Participants reported gMG symptoms that affected many body regions and functions, with an average of 16 symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
6
19
0
Order By: Relevance
“…Of note, 80% of patients in our study were >40 years of age, which may result in a higher rate of comorbidities compared with a younger population. Similarly, the particular symptoms identified in our study are broadly in line with those highlighted in other studies and have previously been reported as the most bothersome 15–17 . The prominence of slurred speech in work‐related domains may reflect the particular importance of effective communication in the workplace, and has not been previously noted.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, 80% of patients in our study were >40 years of age, which may result in a higher rate of comorbidities compared with a younger population. Similarly, the particular symptoms identified in our study are broadly in line with those highlighted in other studies and have previously been reported as the most bothersome 15–17 . The prominence of slurred speech in work‐related domains may reflect the particular importance of effective communication in the workplace, and has not been previously noted.…”
Section: Discussionsupporting
confidence: 92%
“…The positive effects of NMD670, on top of said immunomodulatory treatment, thus further support the idea that ClC-1 inhibition is additive to other types of MG therapies. In a recent study, patients with MG reported that the nature of the fluctuating and often unpredictable symptom severity necessitates better treatment options that allow patients to keep symptoms under control ( 27 ). From the current work, NMD670 appears to have a fast onset of action and good oral bioavailability, adding further value to this new treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study among 165 MG patients found that 40% had stopped working and 20% had changed their occupation due to MG [99]. In a qualitative study from the United States, all 28 MG participants reported impacts on their working activities and financial situation [100].…”
Section: Rehabilitation and Workmentioning
confidence: 99%